2011
DOI: 10.4141/cjss09117
|View full text |Cite
|
Sign up to set email alerts
|

Influence of textural layering on field capacity of coarse soils

Abstract: Zettl, J. D., Barbour, S. L., Huang, M., Si, B. C. and Leskiw, L. A. 2011. Influence of textural layering on field capacity of coarse soils. Can. J. Soil Sci. 91: 133–147. The current method of designing reclamation covers for land disturbed by oil sands mining in northern Alberta, Canada, relies on an estimate of the field capacity (FC) of both natural soils and reclamation soil prescriptions. The objective of this research was to examine the influence of layered, textural heterogeneity on FC. Field testing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 20 publications
3
61
0
Order By: Relevance
“…Past research indicates that layering soils with even minor contrast in soil texture could lead to increased WSC (Zettl et al 2011). However, it is difficult to find different soils in areas where soils are uniform in texture, without transporting soil from one location to another.…”
Section: Discussionmentioning
confidence: 99%
“…Past research indicates that layering soils with even minor contrast in soil texture could lead to increased WSC (Zettl et al 2011). However, it is difficult to find different soils in areas where soils are uniform in texture, without transporting soil from one location to another.…”
Section: Discussionmentioning
confidence: 99%
“…Layering may also be a viable reclamation soil option because it concentrates the seed bank present in the FFMM to the surface layer rather than burying seeds and propagules at depth (MacKenzie and Quideau 2011). Layering also creates a break in the soil column which can result in a greater water holding capacity, an important factor in drier climates such as in northern Alberta (Li et al 2014;Zettl et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The use of multiple amendments in the Demo plot was to test the influence of textural heterogeneity and multi-layered soil capping technique on hydrological processes. This soil capping approach has been demonstrated in several studies in the oil sands region (Barbour et al 2007;Zettl et al 2011). Both the lake sediment and LFH materials were dumped on the Demo plot and mounded using a loader to create a micro-hummocky surface that is intended to promote surface water infiltration and to create micro-sites for vegetation establishment.…”
Section: Description Of Soil Treatmentsmentioning
confidence: 99%
“…This multi-layered soil cover configuration has been widely tested in soil capping prescriptions in the oil sands reclamation research (Barbour et al 2007;Zettl et al 2011). Based on infiltration tests on seven natural coarse-textured sites within the boreal forest in northeastern Alberta, Zettl et al (2011) showed that field capacity moisture contents of topsoils increased with textural heterogeneity, and were directly associated with ecosite productivity.…”
Section: Soil Water Dynamics and Solute Distributionmentioning
confidence: 99%